Phase-Dependent Epitaxy for Antimonene Growth on Silver Substrate - Liu, Kai; Bai, Keke; Wang, Jing; Song, Juntao; Liu, Ying (Frontiers in Physics, 2022)
Antimonene is a novel two-dimensional topological semiconductor material with a strain-driven tunable electronic structure for future electronic devices, but the growth of clean antimonene is not fully understood. In this work, the growth process of antimonene on the silver substrate has been studied in detail by using the density functional theory and particle swarm optimization algorithms. The results show that, in addition to the experimental reported flat honeycomb and β-phase antimonene, α-phase antimonene was observed to be able to grow on the substrates, and the phases of antimonene were deeply dependent on the reconstructed supercells and surface alloys. It has been demonstrated that the surface alloys on the substrate play an active role in the growth of antimonene.